2020
DOI: 10.1016/j.tranon.2020.100868
|View full text |Cite
|
Sign up to set email alerts
|

MET exon 14 skipping mutation, amplification and overexpression in pulmonary sarcomatoid carcinoma: A multi-center study

Abstract: Background High frequency of MNNG HOS transforming ( MET ) exon 14 skipping mutation ( MET exon 14Δ) has been reported in pulmonary sarcomatoid carcinomas (PSCs). However, the frequencies differ greatly. Our study aims to investigate the frequency of MET alterations and the correlations among MET exon 14Δ, amplification, and protein overexpression in a large cohort of PSCs. MET exon 14Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…They are most often encountered in smokers and patients diagnosed with lung adenocarcinoma. They should also be routinely sought in patients with pulmonary sarcomatoid carcinoma (PSC), as their prevalence in this patient group exceeds 7% [ 25 ]. In contrast to most driver mutations occurring in lung cancer, they are most commonly observed in elderly patients (after the age of 70) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…They are most often encountered in smokers and patients diagnosed with lung adenocarcinoma. They should also be routinely sought in patients with pulmonary sarcomatoid carcinoma (PSC), as their prevalence in this patient group exceeds 7% [ 25 ]. In contrast to most driver mutations occurring in lung cancer, they are most commonly observed in elderly patients (after the age of 70) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the MET exon 14 skipping mutation occurred in approximately 3–5% of lung adenocarcinoma cases, slightly more than 2% of squamous cell carcinomas, and 2.3% of other lung cancer histology types ( 6 , 28 , 29 ). Moreover, the MET exon 14 skipping mutation showed a specifically high incidence in lung sarcomatoid carcinomas (approximately 11–30%) ( 7 , 30 ). In the present study, the MET exon 14 skipping mutation occurred in 0.90% (41/4,564) of adenocarcinoma, 1.02% (3/294) of squamous cell carcinoma, and 8.33% (1/12) of sarcomatoid carcinoma specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, METex14 is not correlated with MET overexpression, whereas mixed results surround the correlation between MET amplification and MET overexpression [7,11,24]. Quantification of MET protein levels by immunohistochemistry has shown that increases in MET levels may be present even in the absence of METex14 or MET amplifications [24,31,42].…”
Section: Metex14 Biologymentioning
confidence: 99%
“…A meta-analysis of patients with NSCLC found that among different histologies, METex14 occurred only in ~1% of squamous cell carcinoma, ~2% of adenocarcinoma, ~6% of adenosquamous cell carcinoma, and ~13% of pulmonary sarcomatoid carcinoma cases [6]. In particular, the prevalence of METex14 in pulmonary sarcomatoid carcinomas can be substantial, ranging between 4.9% and 31.8% [4,6,11,12]. Patients with METex14 NSCLC are significantly older than patients with NSCLC without METex14 as well as those with EGFR, KRAS mutations, or ALK rearrangements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation